THE GOVERNMENT'S LEGAL RESPONSIBILITY IN FULFILLING PERSONAL PROTECTIVE EQUIPMENT FOR DOCTORS DURING THE COVID-19 PANDEMIC - Putri Bahari Derma; Ardiansyah Ardiansyah; Sudi Fahmi (Smart Education, 2022)
Abstract: The high rate of Covid-19 infection that occurs today requires the fulfillment of health facilities for doctors and health workers, especially Personal Protective Equipment (PPE) in handling patients during the Covid-19 pandemic. PPE shortages were widely reported in some health care facilities in various regions. Not only in privately owned health service facilities, government hospitals and puskesmas are also not spared from experiencing limited PPE. This Study discusses how the Government's Legal Responsibility Arrangements in Fulfilling PPE (APD) for Doctors amidst the Covid-19 Pandemic. This study used normative legal as its research method. The results of this study indicated that there are no specific arrangements that regulate the government's responsibility in providing PPE (APD) for doctors during the Covid-19 period. The government's responsibility for providing PPE for doctors amidst the covid-19 period was a form of main responsibility. But it was still not done well. Ideally, the governments responsibility in fulfilling physicians rights to health has emerged in accordance with the standards set by WHO in the form of providing appropriate personal protective equipment. It was important to Special monitoring is needed regarding the availability of existing PPE (APD) in the form of quantity and quality so that the safety and health rights of doctors can be fulfilled.Keywords: Job Characteristics, Individual Characteristics, Job Satisfaction, CivilServant Performance.Abstrak: Tingginya angka infeksi Covid-19 yang terjadi saat ini menuntut pemenuhan fasilitas kesehatan bagi dokter dan tenaga kesehatan khususnya Alat Pelindung Diri (APD) dalam menangani pasien di masa pandemi Covid-19. Kekurangan APD dilaporkan secara luas di beberapa fasilitas pelayanan kesehatan di berbagai daerah. Tidak hanya di fasilitas pelayanan kesehatan milik swasta, rumah sakit pemerintah dan puskesmas juga tidak luput mengalami keterbatasan APD. Kajian ini membahas bagaimana Pengaturan Tanggung Jawab Hukum Pemerintah dalam Pemenuhan APD (APD) bagi Dokter di tengah Pandemi Covid-19. Penelitian ini menggunakan hukum normatif sebagai metode penelitiannya. Hasil penelitian ini menunjukkan bahwa tidak ada pengaturan khusus yang mengatur tentang tanggung jawab pemerintah dalam penyediaan APD (APD) bagi dokter selama masa Covid-19. Tanggung jawab pemerintah dalam menyediakan APD bagi para dokter di tengah masa Covid-19 merupakan bentuk tanggung jawab utama. Tapi itu masih belum dilakukan dengan baik. Idealnya, tanggung jawab pemerintah dalam memenuhi hak dokter atas kesehatan telah muncul sesuai dengan standar yang ditetapkan oleh WHO dalam bentuk penyediaan alat pelindung diri yang sesuai. Penting Perlu pemantauan khusus mengenai ketersediaan APD (APD) yang ada dalam bentuk kuantitas dan kualitas agar hak keselamatan dan kesehatan dokter dapat terpenuhi.Kata kunci: Karakteristik Pekerjaan, Karakteristik Individu, Kepuasan Kerja, Sipil Kinerja Pelayan.